Analisis Kritik Sosial terhadap Praktik Pencemaran Laut dalam Novel Flush Karya Carl Hiaasen - Khairunnisa, Aliefia Shatila Diva; Sarjan, Muhammad; Sjah, Taslim (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to examine social criticism of marine pollution practices in Carl Hiaasen's novel Flush (2005) through an ecocritical approach. The novel tells the story of a teenager named Noah who tries to expose illegal waste disposal practices by tour boat owners in the Florida Keys. Through a light but morally charged narrative, Hiaasen criticizes ecological injustice and weak environmental law enforcement. The study uses qualitative methods with content and thematic analysis techniques for the narrative, symbols, and characters in the novel. The results of the study show that Flush represents environmental exploitation as an impact of unequal power relations that are oriented towards economic gain. Characters such as Noah and Paine become symbols of moral courage and resistance to a corrupt system. The symbols of ship waste and polluted seas emphasize that pollution is not merely a technical issue, but also a social and political one. The novel emphasizes the role of the younger generation in environmental conservation. The findings are closely related to the Indonesian context which still faces similar challenges in the management and enforcement of marine pollution laws.